Extranodal marginal zone B‐cell lymphoma of mucosa‐associated lymphoid tissue in the oromaxillofacial head and neck region: A retrospective analysis of 105 patients. (15th November 2019) - Zhang, Tian; Wu, Yunteng; Ju, Houyu; Meng, Jian; Guo, Wei; Ren, Guoxin
Abstract: Background: Extranodal marginal zone B‐cell lymphoma of mucosa‐associated lymphoid tissue (MALT lymphoma) in the oromaxillofacial head and neck region is rare, with limited data available. This retrospective study explored the clinical features, stage, treatment, and prognosis of this disease. Methods: Overall, 105 patients with MALT lymphomas in the oromaxillofacial head and neck region were included in this retrospective analysis. SPSS 22.0 software package was used for data analysis and a two‐tailed P value of ≤.05 was considered statistically significant. Primary endpoints of the study were the complete response (CR) rate, overall survival (OS), and progression‐free survival (PFS). Results: About 52% of the patients had long‐term xerostomia, autoimmune diseases, or chronic parotitis and 81% had diseases involving the large salivary glands. Ann Arbor staging of the patients was as follows: stages I/II, 73 patients and stages III/IV, 32 patients. In the 97 patients followed up, CR rate after initial treatment was 80%. Tumor progression was observed in 12 patients and 14 patients died. There was a significant difference between the rate of CR in localized (87%) and disseminated (67%) lymphoma patients ( P  = .02). The 5‐ and 10‐year PFS of the localized lymphoma patients were both 91%, whereas those of the disseminated lymphoma patients were 83% and 65%, respectively ( P  = .03). The 5‐year PFS rates of the chemotherapy and non‐chemotherapy groups in the disseminated lymphoma patients were 85% and 73% ( P  = .04). Meanwhile, the 5‐year PFS rates of the rituximab and non‐rituximab groups in the disseminated lymphoma patients were 100% and 70% ( P  = .03). In multivariate analysis, MALT Lymphoma International Prognostic Index (MALT‐IPI) was an independent prognostic factor affecting OS, whereas Ann Arbor staging affected PFS. Conclusions: This study suggests that the outcome after initial treatment of MALT lymphomas in the oromaxillofacial head and neck region is satisfactory and that this disease progresses slowly. The CR rate and PFS of localized lymphoma patients are better than those of disseminated lymphoma patients. Systemic treatment (chemotherapy or rituximab) may improve PFS in disseminated disease patients. MALT‐IPI and Ann Arbor staging are independent prognostic factors. Abstract : Systemic therapy may improve survival in disseminated disease patients of MALT lymphomas in the oromaxillofacial head and neck region; MALT‐IPI and Ann Arbor staging are independent prognostic factors.